Home Sweet Israel - Barda, Tal (Israel, 2010)
The story follows Felicia, an undocumented worker managing a kindergarten in her home in southern Tel-Aviv. She cares for dozens of undocumented children, often raising them more than their own migrant parents, all in the shadow of the government campaign to deport them. Her only desire for more than 18 years is to see her daughter whom she left when she was 6 months old in Ghana.
Verzio Film Festival Submission
Keywords: Documentary films